Unleashing Web 2.0 : from concepts to creativity - Vossen, Gottfried (Elsevier/Morgan Kaufmann, 2007)
The emergence of Web 2.0 is provoking challenging questions for developers: What products and services can our company provide to customers and employees using Rich Internet Applications, mash-ups, Web feeds or Ajax? Which business models are appropriate and how do we implement them? What are best practices and how do we apply them? If you need answers to these and related questions, you need this booka comprehensive and reliable resource that guides you into the emerging and unstructured landscape that is Web 2.0. Gottfried Vossen is a professor of Information Systems and Computer Science at the University of Muenster in Germany. He is the European Editor-in-Chief of Elseviers Information SystemsAn International Journal. Stephan Hagemann is a PhD. Student in Gottfrieds research group focused on Web technologies. * Presents a complete view of Web 2.0 including services and technologies * Discusses potential new products and services and the technology and programming ability needed to realize them * Offers how to basics presenting development frameworks and best practices * Compares and contrasts Web 2.0 with the Semantic Web.